Tamiḻ nāṭṭuppuṟa iyal āyvu - Cuppiramaṇiyaṉ, Ca. Vē., 1929- (Publication (International Institute of Tamil Studies) ;, 1979)
Contributed papers on the origin and development of folk lore and folk arts in the districts of Tamil Nadu.